Stylistic classification of “axe-god” jade pendants and its functional aspects: a material analysis conducted at the Museum of Jade, Costa Rica - Kuboyama, Waka (2019)
In this study, we focus on the “axe-god” jade pendants, which dominate the large part of jade artifacts in Costa Rica. These pendants are known that the denomination is not by means of its function as real axes, but its axe-like shape. However, the author thinks that there is a possibility that some of them had been used as tools before or after being reworked for the pendants. The stylistic classification in this study aims to elucidate the functional aspects of the pendants, focusing on their size and shape, then combines these factors with motives. To support the hypothesis of the practical usage of the pendants, detailed analyses with a digital microscope are conducted to see the possible use-wear.